A quantitative tour of the social sciences - Cortina, Jeronimo; Gelman, Andrew (Cambridge University Press, 2009)
Social scientists become experts in their own disciplines but aren't always familiar with what is going on in neighboring fields. To foster a deeper understanding of the interconnection of the social sciences, economists should know where historical data come from, sociologists should know how to think like economists, political scientists would benefit from understanding how models are tested in psychology, historians should learn how political processes are studied, psychologists should understand sociological theories, and so forth. This overview by prominent social scientists gives an accessible, non-technical sense of how quantitative research is done in different areas. Readers will find out about models and ways of thinking in economics, history, sociology, political science, and psychology, which in turn they can bring back to their own work.